Enhancing accounting learning with curriculum and library support at SMK Daarut Tauhiid - Annisa I’zzatul Jannah; Firda Shauma Destiawan; Okta Nurul Gina; Zahra Nabilatu Azkia (Himpunan Pengembang Kurikulum Indonesia, 2025)
The curriculum functions as a tool to achieve educational goals, a good curriculum must be carefully designed to meet the needs of students and society. This research discusses the implementation of the Kurikulum Merdeka at Daarut Tauhiid Vocational School to improve students' accounting skills through In-House Training (IHT), supporting facilities, and project-based learning (PBL) methods. This research aims to analyze the implementation of the Kurikulum Merdeka, identify opportunities and challenges, provide recommendations for optimizing the curriculum, and evaluate the effectiveness of IHT and PBL learning methods in improving student competence. The research used descriptive qualitative methods with data obtained through interviews with deputy principals, accounting teachers, and library staff. The research results show that Daarut Tauhiid Vocational School implements the Kurikulum Merdeka and the foundation curriculum. Teachers and staff receive adequate training so that they can implement learning effectively. The school also provides adequate facilities to support student access to the latest education. Although there are several challenges. Daarut Tauhiid Vocational School has successfully implemented the Kurikulum Merdeka effectively with the support of teacher training, adequate facilities and project-based learning methods. To overcome challenges in implementation, researchers recommend practical optimization of the curriculum to prepare students for the world of work. Abstrak Kurikulum berfungsi sebagai alat untuk mencapai tujuan pendidikan, kurikulum yang baik harus dirancang dengan cermat untuk memenuhi kebutuhan peserta didik dan masyarakat. Penelitian ini membahas implementasi Kurikulum Merdeka di SMK Daarut Tauhiid untuk meningkatkan kemampuan akuntansi peserta didik melalui In-House Training (IHT), fasilitas pendukung, dan metode pembelajaran berbasis proyek (PBL). Penelitian ini bertujuan untuk menganalisis implementasi Kurikulum Merdeka, mengidentifikasi peluang dan tantangan, memberikan rekomendasi optimalisasi kurikulum, dan mengevaluasi efektivitas metode pembelajaran IHT serta PBL dalam meningkatkan kompetensi peserta didik. Penelitian menggunakan metode kualitatif deskriptif dengan data diperoleh melalui wawancara dengan wakil kepala sekolah, guru akuntansi, dan staf perpustakaan. Hasil Penelitian menunjukan bahwa SMK Daarut Tauhiid mengimplementasikan Kurikulum Merdeka bersama kurikulum yayasan. Guru dan staf mendapat pelatihan yang memadai sehingga dapat mengimplementasikan pembelajaran dengan efektif, Sekolah juga menyediakan fasilitas yang memadai untuk mendukung akses peserta didik terhadap keterbaruan pendidikan. Meski terdapat beberapa tantangan. SMK Daarut Tauhiid berhasil menerapkan Kurikulum Merdeka secara efektif dengan dukungan pelatihan guru, fasilitas memadai, dan metode pembelajaran berbasis proyek. Untuk mengatasi tantangan dalam implementasi, peneliti merekomendasikan optimalisasi praktis kurikulum guna mempersiapkan peserta didik menghadapi dunia kerja. Kata Kunci: fasilitas pendidikan; in-house training (IHT); Kurikulum Merdeka; optimalisasi kurikulum; project-based learning (PBL)